A Comparative Study of the Adherent-Invasive Escherichia coli Population and Gut Microbiota of Healthy Vegans versus Omnivores - Rebecca Veca; Christian O’Dea; Jarred Burke; Eva Hatje; Anna Kuballa; Mohammad Katouli (Microorganisms, 2020)
Adherent-invasive Escherichia coli (AIEC) strains carry virulence genes (VGs) which are rarely found in strains other than E. coli. These strains are abundantly found in gut mucosa of patients with inflammatory bowel disease (IBD); however, it is not clear whether their prevalence in the gut is affected by the diet of the individual. Therefore, in this study, we compared the population structure of E. coli and the prevalence of AIEC as well as the composition of gut microbiota in fecal samples of healthy participants (n = 61) on either a vegan (n = 34) or omnivore (n = 27) diet to determine whether diet is associated with the presence of AIEC. From each participant, 28 colonies of E. coli were typed using Random Amplified Polymorphic DNA (RAPD)–PCR. A representative of each common type within an individual was tested for the presence of six AIEC-associated VGs. Whole genomic DNA of the gut microbiota was also analyzed for its diversity profiles, utilizing the V5-V6 region of the16S rRNA gene sequence. There were no significant differences in the abundance and diversity of E. coli between the two diet groups. The occurrence of AIEC-associated VGs was also similar among the two groups. However, the diversity of fecal microbiota in vegans was generally higher than omnivores, with Prevotella and Bacteroides dominant in both groups. Whilst 88 microbial taxa were present in both diet groups, 28 taxa were unique to vegans, compared to seven unique taxa in the omnivores. Our results indicate that a vegan diet may not affect the number and diversity of E. coli populations and AIEC prevalence compared to omnivores. The dominance of Prevotella and Bacteroides among omnivores might be accounted for the effect of diet in these groups.